Closing the abdomen: update on the current surgical toolkit. Issue 2 (14th April 2022) - Amin, Irum; Canovai, Emilio
Abstract : Purpose of review: Achieving abdominal wall closure after intestinal transplantation (ITx) is one of the crucial surgical challenges. This problem is present in 25–50% of all transplants due to reduction in abdominal domain, fistulae and extensive adhesions due to previous surgeries. Failure to achieve closure is an independent risk factor for mortality and graft loss. The aim of this paper is to summarize the current options to achieve this. Recent findings: Successful closure of the abdomen requires a tension-free repair. Primary closure of the fascia can be reinforced with synthetic or biological mesh. For more complex fascial defects bridging mesh, nonvascularised or vascularised rectus fascia can be utilised. If all components of the abdominal wall are affected, then a full-thickness abdominal wall transplantation may be necessary. Summary: A variety of successful techniques have been described by different groups to enable abdominal wall closure after ITx. Emerging developments in preoperative imaging, reconstructive surgery and immunology have expanded the surgical toolkit available. Crucial is a tailor-made approach whereby patients with expected closure issues are identified prior to surgery and the simplest technique is chosen.